Role Structure and Rhytmic Nomenclature of Indang Music in Nagari Tandikek - Hasanul Rizki Febrian; Aditya Dwi Ananda Firdaus; Asril (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to comprehensively describe the internal role structure of performers and the local nomenclature of rhythmic patterns produced by the rapai instrument in the Indang traditional performance within Nagari Tandikek. Utilizing a descriptive qualitative approach with an ethnomusicological perspective, data were gathered through in-depth interviews with a maestro and tukang dikie of Indang, supplemented by direct field observations of drumming techniques. The findings reveal that Indang Tandikek possesses a highly specific and rigid role structure consisting of tukang dikie, tukang karang, tukang darak, tukang lalu, tukang apik, tukang aliah, and tukang panuruikan. Each role fulfills a distinct musical function crucial to maintaining performance continuity. Regarding organology and drumming techniques, the study identifies distinct local interlocking variations: darak panjang serves exclusively as the opening pattern, while the darak pendek group—comprising darak katereang, darak patiang jongkek, and darak tujuah—is played during vocal (dendang) pauses. Furthermore, the overall dynamics and tempo esclations are governed collectively through intuition (feeling) and technical mastery of the primary players rather than strict mathematical counts. This study concludes that the rhythmic complexity of Indang Tandikek functions not only as a visual aesthetic regulator but also as a preservation mechanism for social rhythms through a transmission system rooted in the kulipah (school lineage).